Induction of immunity following vaccination with a chemically attenuated malaria vaccine correlates with persistent antigenic stimulation. Issue 4 (11th April 2018) - Reiman, Jennifer M; Kumar, Sanjai; Rodriguez, Ingrid B; Gnidehou, Sedami; Ito, Koichi; Stanisic, Danielle I; Lee, Moses; McPhun, Virginia; Majam, Victoria; Willemsen, Nicole M; Batzloff, Michael R; Raja, Amber I; et al.
Abstract: Objectives: Blood stage malaria parasites attenuated with seco‐cyclopropyl pyrrolo indole (CPI) analogues induce robust immunity in mice to homologous and heterologous malaria parasites and are being considered for the development of a human vaccine. However, it is not understood how attenuated parasites induce immunity. We showed that following vaccination, parasite DNA persisted in blood for several months, raising the possibility that ongoing immune stimulation may be critical. However, parasites were not seen microscopically beyond 24 h postvaccination. We aimed to provide a mechanistic understanding of immune induction. Methods: Mice were vaccinated with chemically attenuated Plasmodium chabaudi parasites. PCR and adoptive transfer studies were used to determine the presence of parasites and antigen in vivo . In other experiments, Plasmodium falciparum parasitised red blood cells were attenuated in vitro and RNA and antigen expression studied. Results: We show that blood transferred from vaccinated mice into naïve mice activates T cells and induces complete protective immunity in the recipient mice strongly suggesting that there is persistence of parasite antigen postvaccination. This is supported by the presence of parasite RNA in vaccinated mice and both RNA and antigen expression in P. falciparum cultures treated with CPI drugs in vitro . In addition, drugs that block parasite growth also prevent the induction of immunity in vaccinated mice, indicating that some growth of attenuated parasites is required for immune induction. Conclusions: Attenuated parasites persist at submicroscopic levels in the blood of mice postvaccination with the ability to activate T cells and induce ongoing protective immune responses. Abstract : Chemical treatment in vitro is a way to generate attenuated malaria parasites that can be used as a vaccine. We show that attenuated parasites persist in vivo and that this persistence is responsible for ongoing immune induction.